2024
DOI: 10.1057/s41599-023-02590-1
|View full text |Cite
|
Sign up to set email alerts
|

Online vs in-person learning in higher education: effects on student achievement and recommendations for leadership

Bandar N. Alarifi,
Steve Song

Abstract: This study is a comparative analysis of online distance learning and traditional in-person education at King Saud University in Saudi Arabia, with a focus on understanding how different educational modalities affect student achievement. The justification for this study lies in the rapid shift towards online learning, especially highlighted by the educational changes during the COVID-19 pandemic. By analyzing the final test scores of freshman students in five core courses over the 2020 (in-person) and 2021 (onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This information pandemic had resulted in disbelief and over-information among a population that was no longer able to differentiate what was real from what was not. Research of all sorts was carried out all around the world, such as in Latin America with studies on Brazil (Ceron et al, 2021) or Chile (Mellado et al, 2021): in Europe, the case of Spain (Salaverría et al, 2020) and comparisons between countries (Peña Ascacíbar et al, 2021) and in all kinds of fields, such as sports (Estanyol et al, 2023), education (Alarifi and Song, 2024;Nishimura et al, 2024) or communication (Krittanawong et al, 2020).…”
Section: The Rise Of Fake News Since the Covid-19 Pandemicmentioning
confidence: 99%
“…This information pandemic had resulted in disbelief and over-information among a population that was no longer able to differentiate what was real from what was not. Research of all sorts was carried out all around the world, such as in Latin America with studies on Brazil (Ceron et al, 2021) or Chile (Mellado et al, 2021): in Europe, the case of Spain (Salaverría et al, 2020) and comparisons between countries (Peña Ascacíbar et al, 2021) and in all kinds of fields, such as sports (Estanyol et al, 2023), education (Alarifi and Song, 2024;Nishimura et al, 2024) or communication (Krittanawong et al, 2020).…”
Section: The Rise Of Fake News Since the Covid-19 Pandemicmentioning
confidence: 99%
“…Some examples are PowerPoint slides, online lectures, and more recently, virtual and augmented reality (VAR). Research has shown that by introducing digital technology into a learning environment, students' learning efficacy can be increased, resulting in better academic achievements [1,2]. Various educational technologies or equipment have been adopted in school learning, such as touchscreen displays, interactive whiteboards, tablets, video games, smart phone apps, etc.…”
Section: Introductionmentioning
confidence: 99%